A genius loci for Chile - Pino, Bárbara (Base Diseño e Innovación, 2015)
The challenge for nations such as ours is the ability to take our culture, origins, cultural and environmental motivations and transform them into a strong, persuasive, and current expression, broad and powerful enough to be capable of maintaining a dialog with the world. This is the key that will lead us to develop a strong narrative discourse of our creativity based on our territory’s resources, among which is copper.